Virtualisasi Pembelajaran Akidah Akhlak di MI/SD Pada Era New normal : Antara Harapan dan Kenyataan - Nurvina Darise, Gina (Indonesian Journal of Islamic Elementary Education, 2021)
In the new normal era, students are required to change all learning activities from the real world to the virtual world. Likewise, the learning of aqidah akhlak in MI/SD is led to be operationalized through a virtual system using applications or online learning platforms such as: (1) Zoom; (2) Whatsapp; (3) Google Meet; (4) Instagram Live, (5) Youtube; (6) e-books; (7) Google classroom; (8) Weblogs; and (9) e-mail. But on the other hand, there are many problems that occur in the implementation of virtual learning itself, such as the inadequate availability of electricity and internet access as the main media in implementing virtual learning, there are still many teachers who are unable to use technology for virtual learning efficiency, many students whose parents do not have a good economy. established to buy internet quota and smartphones as well as laptops as the main media in participating in this virtual learning. To solve these various problems, strategic steps are needed so that virtual learning becomesof high quality, such as the availability of infrastructure, teacher training and budget allocations to meet financial needs for the good of virtual learning in the current new normal era.